Comparison of intra-amniotic prostaglandin F2 alpha and hypertonic saline for induction of second-trimester abortion. Issue 6022 (5th June 1976) - Unknown
Abstract : The efficacy and safety of intra-amniotic prostaglandin (PG) F2 alpha (25 mg repeated in six hours) and hypertonic saline (200 ml 20% NaC1) were compared in an international multicentre randomised study organised by the World Health Organisation's prostaglandin task force. Both hypertonic saline and PGF2alpha were found to be effective in terminating second-trimester pregnancy. The main advantage of PGF2alpha however, was its greater efficacy, with significantly higher success rates in the first 48 hours. Out of 717 women given PGF2alpha 614 (85-6%) aborted within 48 hours; by 24 hours 439 (61-2%) had aborted, and by 36 hours 574 (80-1%) had aborted. Out of 796 women given hypertonic saline 641 (80-5%) aborted within 48 hours; however, by 24 and 36 hours, respectively, only 161 (20-2%) and 462 (58%) had aborted. Although PGF2alpha was associated with a somewhat higher frequency of minor side effects than hypertonic saline, notably vomiting and diarrhoea, these were within acceptable limits. Only 59 women (8-2%) in the prostaglandin group had more than four episodes of vomiting and 11 (1-5%) more than four episodes of diarrhoea. Ohter side effects occurred only occasionally. No difference was found between the two groups in the frequency of incomplete abortion or excessive bleeding.